Using agile project management in the design and implementation of activity-based costing systems - Jimenez, Victor (2020)
The success of a costing system is dependent on its appropriation and assimilation by the organization. The involvement of all stakeholders from the early stages of design and implementation plays a critical role in this process. In this paper, the use of agile project management is investigated to support the design and implementation of more effective costing systems. A Design Science Research approach was followed to apply an agile project management approach-the Scrum methodology-to the design and implementation of an Activity-Based Costing (ABC) system in a hospital imaging service. The proposed methodology identifies the roles, the events, and the most important artifacts in the design and implementation of costing systems. Research results show that applying agile project management principles contributes to a higher degree of acceptance of the costing system by the operating personnel, as well as by top management. It was also found that a simpler model (result of sprint 5), instead of a more detailed one (proposed for sprint 4), may better fit the interests of the decision makers and the organization's accounting and information systems. Thus, the best costing system is not necessarily the most complete or accurate, but the one that is most useful and adapted to the organization's needs. The definition of the product backlog, the several sprints, and the iterative process were critical in this process. The adoption of the Scrum methodology allowed the design and implementation of an ABC system more adapted to the organization's needs and allowed the early identification of problems that, traditionally, are only perceived at the end of the implementation process, therefore increasing the performance and economic sustainability of organizations.